Leprosy in Yucatan. A historical review from the beginning until today (2016)
Leprosy has been present at the Yucatan Peninsula since ancestral times. In this geographical zone important efforts have been developed to study, understand and treat this infection (strongly linked to biblical punishments), so the objective of this paper is to call attention about the relationship of this disorder with that territory, and the current clinical attention to leprosy patients.